Pulmonary artery sarcoma affecting the pulmonary valve mistaken as pulmonary vasculitis: a case report and comparative literature review - Harry James Smith; Fadi Al-Zubaidi; Daniel Sitaranjan; Steven Chiu; David Jenkins (Journal of Cardiothoracic Surgery, 2024)
Abstract Pulmonary arterial sarcomas (PAS) are rare aggressive tumours occurring mainly in the pulmonary trunk. We report a case of PAS involving the pulmonary trunk wall and valve, with uniform wall thickening which represents an atypical imaging manifestation of this tumour. A 63-year-old male presented with vague respiratory symptoms with rapid progression. CTPA showed low density filling defects in both pulmonary arteries and PET scan showed increased uptake in the pulmonary trunk, which along with raised ESR suggested Pulmonary Vasculitis. Echo imaging showed Right ventricular hypertrophy and pulmonary stenosis. Response to steroid therapy was minimal and his symptoms worsened. A referral for second opinion was made and he was diagnosed with PAS. He underwent Pulmonary thromboendarterectomy with Pulmonary valve replacement. Post-operative histopathology confirmed the diagnosis. PAS is rare and frequently misdiagnosed. Surgical resection is not curative, but together with chemotherapy can prolong survival.